2009
DOI: 10.1103/physrevb.80.121402
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of the asymmetric lateral Casimir force between corrugated surfaces in the nonadditive regime

Abstract: The measurement of the lateral Casimir force between two aligned sinusoidally corrugated Au-coated surfaces has been performed in the nonadditive regime. The use of deeper corrugations also allowed us to demonstrate an asymmetry in the phase dependences of the lateral Casimir force, as predicted earlier. The measurement data are found to be in excellent agreement with the exact theoretical results computed at T = 300 K including effect of real material properties. The deviations between the exact theory and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
211
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 119 publications
(219 citation statements)
references
References 21 publications
6
211
2
Order By: Relevance
“…[45][46][47][48]52 It was claimed that anomalous dependences of the residual potential difference and separation on contact on the separation distance observed in several experiments cast doubts on the measurements of the Casimir force performed to date. It was also suggested that inasmuch electrostatic calibrations are based on a fitting procedure there is no principal difference detween independent measurements of the Casimir force [20][21][22][23][24][25][26][27][28][29][30][35][36][37][39][40][41][42][43][44]71 and deriving the Casimir force by means of a fit from some much larger measured force of hypothetical origin. 31 In this respect we would like to note that the calibration consists in determination of the parameters of a setup using well established physical laws (in our case of electrostatics) and involves only well understood and precisely measured forces.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[45][46][47][48]52 It was claimed that anomalous dependences of the residual potential difference and separation on contact on the separation distance observed in several experiments cast doubts on the measurements of the Casimir force performed to date. It was also suggested that inasmuch electrostatic calibrations are based on a fitting procedure there is no principal difference detween independent measurements of the Casimir force [20][21][22][23][24][25][26][27][28][29][30][35][36][37][39][40][41][42][43][44]71 and deriving the Casimir force by means of a fit from some much larger measured force of hypothetical origin. 31 In this respect we would like to note that the calibration consists in determination of the parameters of a setup using well established physical laws (in our case of electrostatics) and involves only well understood and precisely measured forces.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…First, we briefly consider the preparation of the sphere which was done similar to previous experiments. [20][21][22]27,28,39,40,43,44 We used a polystyrene sphere which was glued with silver epoxy (20 × 20 µm 2 spot) to the tip of a triangular silicon nitride cantilever with a nominal spring constant of order 0.01 N/m. The cantilever-sphere system was then coated with a 10 nm Cr layer followed by 20 nm Al layer and finally with a 105 ± 1 nm Au layer.…”
Section: B Sample Preparation and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…For λ smaller than a few micrometers the strongest constraints on the Yukawa-type corrections to Newtonian gravity follow from measurements of the Casimir force [14,15] which becomes the dominant background force in place of gravitation at sufficiently short separations between the test bodies (see review [16]). Measurements of the lateral Casimir force between sinusoidally corrugated surfaces of a sphere and a plate by means of an atomic force microscope (AFM) [17,18] and the gradient of the Casimir force between smooth surfaces of a sphere and a plate by means of a micromachined oscillator [19,20] have already resulted [21] in up to several orders of magnitude stronger constraints.…”
mentioning
confidence: 99%
“…2,5 Independent on separation contact potential was also reported in experiments by U. Mohideen. 2,4,5,[23][24][25] It is notable that all these experiments were performed in high vacuum with small spheres of order 100 µm curvature radii.…”
Section: Anomalies In Electrostatic Calibrationsmentioning
confidence: 99%